Simulation and Experiment of a Medium-Distance Underwater Ultrasonic Wireless Power Transfer System - LIAO, Chenyu; ZHANG, Huaiqing; LI, Zhi; ZHANG, Qian (Archives of Acoustics, 2025)
This paper focuses on ultrasonic wireless power transfer (UWPT), a form of underwater wireless power transfer (WPT) using acoustic (ultrasonic) waves. We propose an ultrasonic transducer designed based on the Langevin transducer model, along with its equivalent circuit model for underwater transmission, tailored for efficient medium-distance underwater WPT. The performance of this transducer is simulated and analyzed using the acoustic-piezoelectric structure module in COMSOL. The results demonstrate that the transducer exhibits excellent underwater transmission characteristics. Additionally, an equivalent circuit model of the underwater UWPT system is developed and analyzed to characterize its transmission properties. For validation, a prototype UWPT is fabricated. At a 35 cm separation between the transmitter and receiver, the transmitter power is 2.5 W. With a 1.2 kΩ load, the received root mean square (RMS) voltage is measured at 22.8 V, corresponding to a received power of 433mW and a transmission efficiency of 17 %. These results verify the proposed model, demonstrate a significant improvement in the transmission distance of underwater UWPT systems, and confirm the feasibility of medium-distance UWPT.